MANAGEMENT STRATEGIES TO ENHANCE TEACHER EMPOWERMENT IN ELEMENTARY SCHOOLS* - Suteeku, Sumalee; Siribanpitak, Pruet; Siripirom, Walaiporn (Scholar: Human Sciences, 2015)
The objectives of this research were 1) to study the current and desirable state of the management to enhance teacher empowerment in elementary schools 2) to analyze strengths, weaknesses, opportunities and threats of the management to enhance teacher empowerment in elementary schools and 3) to develop management strategies for enhancing teacher empowerment in elementary schools. The study was mixed method research. The samples were 395 elementary schools. The instruments used in this study were the questionnaire and the strategic evaluation form of feasibility and appropriateness. The data were analyzed by frequency, percentage, average, standard deviation, PNIModified and content analysis. The results showed that 1) The current state of the management to enhance overall teacher empowerment in elementary schools were at the high level. The empowerment of individual was higher than the group empowerment (x=4.0641 and 4.0249 respectively). The desirable state of the management to enhance overall teacher empowerment in elementary schools were at the highest level. The empowerment of individual was higher than the group empowerment (x=4.5159 and 4.5019 respectively). 2) The strengths of the management to enhance the empowerment of teacher in elementary schools was the empowerment of individuals. The weaknesses of the management to enhance the empowerment of teacher in elementary schools was the empowerment of group. Opportunity for the management to enhance the empowerment of teachers in elementary schools was government policy and technology, the threat of the management to enhance the empowerment of teachers in elementary schools was the economic and society. 3) The management strategies to enhance the empowerment of teachers in elementary schools were (1) Enrich the strengths and opportunities, coupled with the reduction of weaknesses and prevention of threats to individual empowerment (2) Enrich the opportunities coupled with the reduction of weaknesses and prevention of threats to group empowerment.